Characteristics of polar cusp VLF emissions observed by ISIS satellites of low altitude polar orbit - Ondoh, Tadanori (National Institute of Polar Research, 1997)
P(論文) Characteristics of polar cusp hiss and other VLF emissions observed in the cusp region are studied by using f-t spectra and narrow-band intensity data at six frequencies which were processed from VLF electric field data received from ISIS-1 and ISIS-2 at Syowa Station, Antarctica. The polar cusp hiss is very irregular in frequency, intensity and time (or space), and shows fine intensity variations in the narrow-band intensity data at 5 and 8kHz bands as compared with coarse intensity variations of the polar hiss (or auroral hiss) appearing on either side of the polar cusp region. The polar cusp hiss occurs over several hours centered around the geomagnetic noon in geomagnetic local time for a few minutes in UT on ISIS west to east passes. The regions of polar hiss with curtain-like f-t spectrum lie on both sides of the polar cusp hiss region. The irregular and structured spectra of polar cusp hiss and saucer emissions may reflect irregular and structured electron precipitations in the cusp region. The polar cusp VLF emissions, such as the polar cusp hiss and VLF saucers occur at invariant latitudes from 72°to 86°, and at geomagnetic local times from 09 to 15 hours. The polar cusp VLF hiss is discussed in terms of the whistler-mode cherenkov radiations generated from downgoing electrons in the polar magnetosphere. departmental bulletin paper